"The sky seems heavy with clouds": Arthur S. Eddington and the IAU. Issue Volume 13:Issue S349(2018) (1st April 2019) - Laguens, Florian
Abstract: This paper addresses the relationships between Arthur S. Eddington, former director of the Cambridge Observatory (1914-1944), with the International Astronomical Union. It is demonstrated that the Union was related to every major moment in Eddington's scientific career. New historical elements are brought forward, in the last section of the paper, to demonstrate Eddington's action in favour of German colleagues during the Second World War.